Chemical Warfare during the Vietnam War : Riot Control Agents in Combat. - Ellison, D. Hank (Taylor & Francis, 2011)
Chemical Warfare during the Vietnam War documents the use of antipersonnel chemical weapons throughout the Vietnam War, and explores their effectiveness under the wide variety of circumstances in which they were employed. The short, readable account follows the US program as it progressed from a focus on the humanitarian aspects of non-lethal chemicals to their use as a means of increasing and enhancing the destructiveness of traditional weapons. It also presents the efforts of the North Vietnamese to both counter US chemical operations and to develop a chemical capability of their own. This l.